Echoes of the “Keraton”: Translating Javanese Court Culture for local and Global Viewers - Asmarani, Rahmanti; Bayu Ade Prabowo; Sri Oemiati (Eduvelop: Journal of English Education and Development, 2025)
This study analyzes translation strategies employed in subtitling the "Marak" short film from Javanese to Indonesian and English, focusing on challenges of translating Javanese court culture for dual audiences with different cultural proximities to the source culture. Using qualitative descriptive approach with content analysis, the research examines 47 cultural terms across three subtitle versions, categorizing them according to Newmark's cultural classification framework and analyzing translation strategies through integrated theoretical frameworks of Gottlieb's subtitling strategies, Pedersen's cultural reference translation strategies, and Venuti's foreignization-domestication paradigm. The findings reveal significant differences in translation approaches between target languages: Indonesian translations predominantly employ transfer/retention strategies (59.57%), indicating cultural preservation orientation, while English translations favor direct translation (31.91%) and specification (25.53%) strategies, demonstrating accessibility orientation for international audiences. Social culture terms dominate the cultural vocabulary at 38.30%, reflecting the central importance of hierarchical relationships and honorific language in Javanese court interactions. The research contributes empirical evidence that effective dual-audience cultural translation requires strategic differentiation based on audience cultural proximity rather than uniform translation solutions, with implications for audiovisual translation practice and cultural preservation in contemporary media contexts.